Modeling of the cold electron plasma density for radiation belt physics - Ripoll, J.-F.; Pierrard, V.; Cunningham, G. S.; Chu, X.; Sorathia, K. A.; Hartley, D. P.; Thaller, S. A.; Merkin, V. G.; Delzanno, G. L.; De Pascuale, S.; Ukhorskiy, A. Y. (Frontiers in Astronomy and Space Sciences, 2023)
This review focusses strictly on existing plasma density models, including ionospheric source models, empirical density models, physics-based and machine-learning density models. This review is framed in the context of radiation belt physics and space weather codes. The review is limited to the most commonly used models or to models recently developed and promising. A great variety of conditions is considered such as the magnetic local time variation, geomagnetic conditions, ionospheric source regions, radial and latitudinal dependence, and collisional vs. collisionless conditions. These models can serve to complement satellite observations of the electron plasma density when data are lacking, are for most of them commonly used in radiation belt physics simulations, and can improve our understanding of the plasmasphere dynamics.